HISTOPATHOLOGICAL SPECTRUM OF THYROID LESIONS IN THE SOUTH-WEST PART OF PUNJAB- A TERTIARY CARE CENTER STUDY - JASMINE KAUR; ARNAV KR ROYCHOUDHURY; NIKITA GOYAL; ANSHUL GUPTA; VIJAY SURI (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The objective is to study histomorphological patterns of thyroid lesions and to classify various thyroid malignant neoplasms according to the World Health Organization (WHO) classification. Methods: The present observational study was done in the department of pathology in a tertiary care institute in 254 thyroid specimens to study histomorphological patterns of thyroid lesions and to classify various thyroid malignant neoplasms according to the WHO classification over 7 years from January 01st, 2010 to December 31st, 2016. Results and Discussion: The most common age group affected was between the 2nd and 3rd decades. Females were more commonly affected than males and females: Male was 5:1. of the 254 cases, 221 were nonneoplastic and 33 were neoplastic. Among nonneoplastic lesions, the most common lesion was multinodular goiter with 121 (47.63%) cases, followed by Colloid goiter 63 (24.80%), adenomatoid goiter- 19 (7.48%), lymphocytic thyroiditis/Hashimoto’s thyroiditis (HT) 17 (6.69%) and only 1 (0.39%) case was found to be of thyroglossal cyst. Among neoplastic lesions, follicular adenoma-24 (9.45%) was the most common lesion, then papillary carcinoma-7 (2.76%) cases, of which 2 (0.79%) were follicular variants of papillary carcinoma, medullary carcinoma - 1 (0.39%), and paraganglioma only 1 (0.39%) case. Conclusion: The histological spectrum of thyroid diseases in the Malwa Region, Punjab, is similar to that seen around the globe and the region. Iodine deficiency has been identified as a significant public health problem, especially in the Sub Himalayan region of India. The consequences of persisting iodine deficiency are goiter, hyperavidity of the thyroid for iodide, and subclinical hypothyroidism during pregnancy and early infancy. Similarly, clinical evaluation of goiter should be thorough and use all means, especially histopathological study of the specimens, to arrive at a definitive diagnosis, as thyroid carcinoma is not uncommon.